Individual work of students of music&pedagogical departments at the analysis of choral works in the classroom for choral conducting (Pedagogy of Higher and Secondary Education, 2013)
Kokareva E. A. Individual work of students of music&pedagogical departments at the analysis of choral works in the classroom for choral conducting.The article deals with the problem of independent work of students of music and pedagogical department on the analysis of choral works; makes the search of effective ways of its decision; discloses specifics of the musical material in classes on choral conducting.
Keywords: students’ individual work; analysis of choral works; musical material; choral conducting